Vitamin D supplementation in obese type 2 diabetes subjects in Ajman, UAE: a randomized controlled double-blinded clinical trial - Sadiya, A; Ahmed, S M; Carlsson, M; Tesfa, Y; George, M; Ali, S H; Siddieg, H H; Abusnana, S (European journal of clinical nutrition, 2015)
Objectives: To study the effect of Vitamin D 3 supplementation on metabolic control in an obese type 2 diabetes Emirati population. Methods: This randomized double-blind clinical trial was conducted with 87 vitamin D-deficient obese, type 2 diabetic participants. The vitamin D-group ( n =45) and the placebo group ( n =42) were matched for gender, age, HbA1c and 25-hydroxy vitamin D (25(OH) D) at the baseline. The study was divided into two phases of 3 months each; in phase 1, the vitamin D-group received 6000 IU vitamin D 3 /day followed by 3000 IU vitamin D 3 /day in phase 2, whereas the placebo group ( n =42) received matching placebo. Results: After supplementation, serum 25(OH) D peaked in the vitamin D-group in phase 1 (77.2±30.1 nmol/l, P =0.003) followed by a decrease in the phase 2 (61.4±18.8 nmol/l, P =0.006), although this was higher compared with baseline. In the placebo group, no difference was observed in the serum 25(OH) D levels throughout the intervention. Relative to baseline serum, parathyroid hormone decreased 24% ( P =0.003) in the vitamin D-group in phase 2, but remained unchanged in the placebo group. No significant changes were observed in blood pressure, fasting blood glucose, HbA1c, C-peptide, creatinine, phosphorous, alkaline phosphatase, lipids, C-reactive protein or thyroid stimulating hormone concentrations compared with baseline in either group. Conclusions: Six months of vitamin D 3 supplementation to vitamin D-deficient obese type 2 diabetes patients in the UAE normalized the vitamin D status and reduced the incidence of eucalcemic parathyroid hormone elevation but showed no effect on the metabolic control.